MODIFICATION OF ASPHALT MIXES USING WHITE CEMENT DUST AND IRON FILINGS AS A FILLER (Advances in Civil and Architectural Engineering, 2021)
The possibility of using white cement dust and iron filings as fillers to modify asphalt mix properties was investigated. Numerous aggregate tests were conducted, including sieve analysis, specific gravity, absorption, and abrasion tests. Several bitumen tests were also conducted, including penetration, softening point, ductility, flash point, and specific gravity tests. Marshall properties were used to evaluate the physical performance of the mixtures. The construction of pavements with iron filings in hot asphalt mixtures is not recommended, but white cement dust powder or limestone powder can be beneficial. A 5% content was observed to be the best white cement dust content. There is no clear relationship between air voids and the percentages of white cement dust and iron filings, as the curve fluctuates. The use of white cement dust as a filler always exhibits better results; therefore, using white cement dust widely is recommended over using iron filings.